Good practices recommendations from the Brazilian Society of Nephrology to Peritoneal Dialysis Services related to the new coronavirus (Covid-19) epidemic - Calice-Silva,Viviane (2020)
ABSTRACT Considering the new coronavirus epidemic (Covid-19), the Brazilian Society of Nephrology, represented by the Peritoneal Steering Committee, in agreement with the and the Dialysis Department, developed a series of recommendations for good clinical practices for peritoneal dialysis (PD) clinics, to be considered during the period of the Covid-19 epidemic. We aim to minimize the disease spread, protecting patients and staff, and ensuring the quality of the treatment provided and adequate follow-up for PD patients. The recommendations suggested at this moment must be adapted to each clinic’s reality and the conditions of the structural and human resources, dependent on the adequate financial provision of the public health system for its full implementation.